Simulation of TAZ:Ir(ppy)3-BCP/ZnO heterostructure OLED. (2023) - Ritu,; Quraishi, A.M.; Kattayat, Sandhya; Josey, Smitha; Alvi, P.A.
Abstract: In this article, we report the temperature dependent I-V characteristics of TAZ:Ir(ppy)3-BCP/ZnO heterostructure based OLED. In addition, we have also optimized the thickness of the ETL (electron transport layer) of the designed OLED. For the optimized ETL (ZnO layer) we have simulated the I-V characteristics, Voltage vs light flux curves and current density vs light flux curves. From such simulation study, it has been found that the designed OLED can work properly at the room temperature with the operating voltage ∼ 4.25 V. Further, the optimized ETL thickness in the TAZ:Ir(ppy)3-BCP/ZnO heterostructure based OLED should be 50 or 60 nm for proper operation and for getting the noticeable light flux.